A potential strategy to rebuild the tumor immune microenvironment: PANoptosis - Wu, Siyu; Tian, Boyan; Pang, Xueying; Sui, Bowen (Frontiers in Immunology, 2025)
The convergence and interplay of pyroptosis, apoptosis, and necroptosis have led to the conceptualization of PANoptosis, an innovative paradigm of inflammatory programmed cell death. Characterized by the hierarchical assembly and activation of the PANoptosome, PANoptosis operates through tightly orchestrated signaling hubs and is intricately linked to organelle functionality. Accumulating evidence underscores its pivotal role in diverse oncogenic processes, positioning PANoptosis as a compelling frontier for antitumor therapeutic exploration. This review delineates the mechanistic underpinnings of PANoptosis, synthesizes its established contributions to tumor progression, and examines its dynamic crosstalk with the tumor immune microenvironment (TIME). Notably, we highlight recent breakthroughs in PANoptosis-driven immunotherapeutic strategies. We further propose that targeting PANoptosis to reprogram TIME represents a transformative approach in oncology, shifting the research paradigm from unimodal cell death regulation to multidimensional intervention. This perspective not only advances fundamental understanding but also holds significant promise for clinical translation, heralding a new era in cancer therapeutics.